Anti-hypertensive and anti-oxidant activities of walnut almond oil, and corn and candesartan on L-NAME induced hypertensive rats - Mohammed, Saman H.; Hussein, Ridha H. (Sulaimani Journal for Pure and Applied Sciences, 2020)
The present study aims to investigate the effects of almond oil, walnut oil, corn, and candesartan on the blood pressure (BP) and some biochemical parameters in L-NAME-induced hypertensive rats. Hypertension was induced experimentally by administration of L-NAME (40 mg/kg of body weight) dissolved in water by gavage. The animals were randomly divided into six groups: normal control, hypertensive (HT), HT+ Walnut oil (3ml/kg body weight), HT+ Almond oil (3 ml/kg body weight), HT+ Candesartan (3mg/kg body weight) by gavage, and HT+ Corn (%30 of diet), At the end of the experiments blood sample were taken from rats by heart puncture. The results indicated that administration with L-NAME induced hypertension after four weeks in rats by significantly increasing the BP, and significant elevation in the level endothelin1(ET-1), angiotensin I-converting enzyme (ACE), and serum malondialdehyde (MDA) were observed. Whereas the levels of nitric oxide (NO) and reduced glutathione (GSH) decreased. Supplementation of walnut oil, corn, and candesartan for three weeks was significantly reduced blood pressures, ACE, ET1, and MDA and a non-significant decrease in ACE concentration by candesartan. While hypertensive rats treated with walnut oil and corn showed significant elevation of NO, GSH. But almond oil supplementation diminished MDA and GSH concentrations. Finally, the results revealed that corn more effectively than walnut oil and near the action of candesartan while almond oil non-significant effect on hypertension.
Keywords: L-NAME; Hypertension; Endothelial dysfunction; Natural oils